2018
DOI: 10.1111/ajt.14914
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric en bloc kidney transplantation from very small (≤10 kg) donation after circulatory death (versus brain death) donors: Single-center matched-pair analysis of 130 transplants

Abstract: En bloc kidney transplants (EBK) from very small pediatric donation after circulatory death (DCD) donors are infrequent because of the perception that DCD adversely impacts outcomes. We retrospectively studied 130 EBKs from donors ≤10 kg (65 consecutive DCD vs 65 donation after brain death [DBD] transplants; pair-matched for donor weight and terminal creatinine, and for preservation time). For DCD vs DBD, median donor weight was 5.0 vs 5.0 kg; median recipient age was 57 vs 48 years (P = .006). Graft losses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…The main limitation of this study is the small cohort size, yet this is the largest reported single‐center series of EKT from donors weighing less than 5 kg, including neonatal donors outside the United States . This study includes the previously reported cases by the author .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of this study is the small cohort size, yet this is the largest reported single‐center series of EKT from donors weighing less than 5 kg, including neonatal donors outside the United States . This study includes the previously reported cases by the author .…”
Section: Discussionmentioning
confidence: 99%
“…The same group also reported a higher risk (10 of 52) of graft thrombosis in EKTs from donors <5 kg compared to ≥5 kg donor EKT (7 of 140) . Their single‐center series of EKTs from 65 paired donation after cardiac death (DCD) and donation after brain death (DBD) donors under 10 kg reported recently states 1‐ and 5‐year death censored graft survival of 89% and 87%, respectively, for DCD grafts and 91% for DBD grafts at 1 and 5 years …”
Section: Introductionmentioning
confidence: 99%
“…Recipients for the en bloc grafts in this analysis were selected according to previously described criteria . With respect to the urinary outflow tract, these criteria included inasmuch as possible preserved urine output (and thus preserved bladder size) in order to maximize likelihood of a tension‐free ureteroneocystostomy.…”
Section: Methodsmentioning
confidence: 99%
“…Data from the United States evaluating outcomes from donors under 10 kg, and comparing DBD vs DCD, also show comparable results, concluding that DCD impacted early post‐transplant graft function, but did not appear to impart added risk for graft loss or long‐term function. Therefore, very small en bloc kidney donors should be considered as an option to augment the deceased kidney donor pool …”
Section: Other Non‐standard Criteria Donorsmentioning
confidence: 99%
“…Data from the United States evaluating outcomes from donors under 10 kg, and comparing DBD vs DCD, also show comparable results, concluding that DCD impacted early post-transplant graft function, but did not appear to impart added risk for graft loss or longterm function. Therefore, very small en bloc kidney donors should be considered as an option to augment the deceased kidney donor pool 65. Patients with current non-CNS tumors are usually excluded for donation (except for cervical carcinoma in situ and non-melanoma skin tumors), while donors with a history of non-CNS tumors are accepted if curative therapy has been successfully performed 10 years prior to donation (except for breast cancer/melanoma).…”
mentioning
confidence: 99%